The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1055/a-2159-6016
|View full text |Cite
|
Sign up to set email alerts
|

Inhalationsanästhesie bei der Katze: Die Entwicklung des Cuffdrucks bei Verwendung von Lachgas

Franziska Benesch,
Frauke Paul,
Michaele Alef

Abstract: Zusammenfassung Gegenstand und Ziel Die Verwendung eines Lachgas-/Sauerstoff-Gemischs bei einer Inhalationsanästhesie führt durch Diffusion von Lachgas in die Blockmanschette des Endotrachealtubus (Cuff) zu einem Anstieg des Drucks im Cuff, wenn dieser, wie üblich, mit Luft gefüllt wurde. Ziel der vorliegenden Studie war, die Entwicklung des Cuffdrucks während einer Isofluran-Lachga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…They observed a rapid increase in ETT cuff pressures in the N 2 O group after the first 15 minutes and showed that the pressures increased to 45 cmH 2 O and above. [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed a rapid increase in ETT cuff pressures in the N 2 O group after the first 15 minutes and showed that the pressures increased to 45 cmH 2 O and above. [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrous oxide (N 2 O), a gas anesthetic used in routine anesthesia, can quickly enter ETT cuffs and increase cuff pressure by diffusing into dead spaces [5,6]. The formation of tracheal mucosal lesions causes sore throat, hoarseness, and cough due to an increase in cuff pressure.…”
Section: Introductionmentioning
confidence: 99%